Education as tradition: relationship adult-child in cultural anthropology from Margaret Mead's and Ruth Benedict's works - Karina Augusta Limonta Vieira (Universidade Federal de Santa Catarina, 2019)
The child has been part of educational and anthropological researches in last decade in Brazil. This paper aims to show education as tradition in the anthropological perspective. Moreover, this paper also aims to discuss in an original way the education as tradition for understanding the relationships adult-child in a perspective of the contributions of cultural anthropology. The paper puts the following questions: what isthe place of adult and child in perspective of cultural anthropology from Mead's and Benedict's works? There is an educational dynamism in dialogue between adult and child? This relationship adult-child in perspective of education as tradition is represented hier in Margared Mead's and Ruth Benedict's works developed at the start of twentieth century. The works show existence of patterns of culture, preservation of relationships and formation of the ideal adult through intergenerational education.